Knowledge on febrile convulsion among the parents of under-five children attending for vaccination in Jaffna MOH clinics - Marin Difna, M.; Dileetha, E.; Kamalarupan, L.; Sanchayan, K. (University of Jaffna, 2024)
Introduction: Febrile convulsion, a common neurological disorder in under-five children, can be distressing for parents. Inadequate awareness of parents may hinder effective management. Objective: To assess the knowledge on febrile convulsion among the parents of under- five children attending for the vaccination in Jaffna MOH clinics. Methodology: An institutional-based descriptive cross-sectional study was carried out among 422 parents of under-five children attending for the vaccination in Jaffna MOH clinics. A pretested and validated interviewer-administered Tamil questionnaire was used to collect the data. Data was analyzed by using SPSS version 27 and presented through mean, standard deviation, frequency, and percentage. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Results: The mean age of the participants was 31 years (SD- 5.237). The male-to-female ratio was 1:3. The mean knowledge score of them was 20.41 (SD- 3.948) out of a total knowledge score of 36. Notably, 36.5% reported that they had personal experience with febrile convulsions, mostly coinciding with their child's experience. The most common age of occurrence of febrile convulsion is from 6 months to five years was identified by half of them. The common risk factors identified by them were: high fever (71.1%), viral infection (48.1%) and family history of febrile convulsion (43.8%). Major symptoms identified by many were: teeth clenching (77%), saliva drooling (77%), muscle twitching (59%) or stiffening (61.6%), and loss of consciousness (50.2%). Nearly half believed every child with febrile convulsions would experience a future episode. Misconceptions regarding management techniques, such as position the patient to the left lateral side (alongside other actions like immobilization, shaking, using metal rods, and mouth-to- mouth resuscitation), underscore the importance of specific and focused education on these topics. Conclusions: Study findings emphasize the crucial requirement for focused education to improve parental comprehension of febrile convulsions and its management.
Keywords: Febrile convulsion; Knowledge; Fever